Magic, witchcraft, and ghosts in the Greek and Roman worlds : a sourcebook - Ogden, Daniel (OUP E-Books., 2002)
In a culture where the supernatural possessed an immediacy now strange to us, magic was of great importance both in the literary mythic tradition and in ritual practice. In this book, Daniel Ogden presents 300 texts in new translations, along with brief but explicit commentaries. Authors include the well known (Sophocles, Herodotus, Plato, Aristotle, Virgil, Pliny) and the less familiar, and extend across the whole of Graeco-Roman antiquity.